Produção de enzimas e bioetanol a partir de matérias-primas amiláceas e resíduos de hortifruti - Devos, Rafaela Julyana Barboza (2022)
Strategies to reduce the use of fossil products that contribute to the emission of greenhouse gases and climate change are constantly evaluated. The use of biofuels such as bioethanol enables clean and sustainable combustion compared to fossil fuels. To integrate the concept of circular bioeconomy, the production of saccharifying enzymes produced by microorganisms isolated from waste is a differential for the conversion of bioethanol. Two bacteria (B1 and B2) and two fungi (F1 and F2) previously isolated from fruit and vegetable residues capable of simultaneously producing amylolytic and cellulolytic enzymes were studied. The bacterial enzyme complex produced by submerged fermentation, when compared to the enzymes produced by fungi via solid-state fermentation, showed higher efficiency of enzymatic activity. The best enzyme production condition was defined by the medium containing whole grain triticale flour and sugarcane bagasse, at pH 5.5. The bacterial enzymes produced in this condition were evaluated in different pH and temperature ranges, aiming at the application in the biotechnology industry. The amylolytic and cellulolytic enzymes produced by B1 showed better performance at pH 5.0 to 5.5 and temperatures of 40 ºC. These results are effective because the enzymes work together, reducing pH and temperature adjustment steps during the process. The enzyme complex produced by B2 showed potential due to its performance at pH 5.0-5.5 at temperatures of 30-50 ºC. However, optimizations in enzyme production are necessary to obtain better results of the amylolytic and cellulolytic activity. Contributing to a sustainable economy and reducing the waste of fruit residues, was studied the production of bioethanol from banana and papaya residue, associated with triticale. The conversion took place with simultaneous saccharification and fermentation (SSF) and separate saccharification and fermentation (SHF). The efficiency and productivity of bioethanol were calculated in each mode of operation and SSF gave significantly higher results (p>0.05) under the conditions evaluated. The substrates were shown to contain the nutrients necessary for the conversion, eliminating the need for additional supplementation, and reducing process costs. The banana residue showed potential and high concentrations and productivity of bioethanol (30.70 g/L; 2.56 g/Lh, respectively, for SSF and 25.68 g/L; 1.95 g/Lh, respectively, for SHF). Waste from this source can be minimized with the production of a high value-added product. However, the addition of the raw materials combined in the experiments gave a dilution to the medium, comprising a bottleneck of the process. Thus, it is necessary to evaluate solutions that minimize the production of water from the mixture and allow maximizing the production of bioethanol from fruit and triticale residues. In SSF, the maximum concentrations of bioethanol for all experiments were identified at 12 h, demonstrating that SSF allows reducing time, energy, and investments, optimizing the process compared to SHF. Given the results, the possibility of production on a laboratory scale is demonstrated, integrating the first and second generations of bioethanol, combining lignocellulosic residues and starchy material, which can reduce the disposal of fruit residues and send them to the biorefinery, integrating the concept of bioeconomy circular.